2015
DOI: 10.1139/apnm-2015-0056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moderate exercise on peritoneal neutrophils from juvenile rats

Abstract: Previous studies showed that moderate exercise in adult rats enhances neutrophil function, although no studies were performed in juvenile rats. We evaluated the effects of moderate exercise on the neutrophil function in juvenile rats. Viability and neutrophils function were evaluated. Moderate exercise did not impair the viability and mitochondrial transmembrane potential of neutrophils, whereas there was greater reactive oxygen species production (164%; p < 0.001) and phagocytic capacity (29%; p < 0.05). Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In terms of activity and function, physical exercise typically induces an initial activation of neutrophils. This is demonstrated through the release of enzymes (172, 173) and subsequent changes in crucial effector functions, including phagocytosis and respiratory burst activity (174,175). Acute exercise has been shown to attenuate neutrophil apoptosis, possibly by its action on the inducible nitric oxide synthase (iNOS)nitric oxide (NO)-cyclic guanosine monophosphate (cGMP)myeloid cell leukemia 1 (Mcl-1) pathway (176), as well as calcium and redox signaling (177).…”
Section: Neutrophilsmentioning
confidence: 99%
“…In terms of activity and function, physical exercise typically induces an initial activation of neutrophils. This is demonstrated through the release of enzymes (172, 173) and subsequent changes in crucial effector functions, including phagocytosis and respiratory burst activity (174,175). Acute exercise has been shown to attenuate neutrophil apoptosis, possibly by its action on the inducible nitric oxide synthase (iNOS)nitric oxide (NO)-cyclic guanosine monophosphate (cGMP)myeloid cell leukemia 1 (Mcl-1) pathway (176), as well as calcium and redox signaling (177).…”
Section: Neutrophilsmentioning
confidence: 99%
“…Physical exercise was used for rodents (running on a motorized treadmill; INSIGHT, model EP-131). Each familiarization session included placing the rats on the treadmill switched off for 10 min and then turning on the treadmill at 8 m/min for 5 min [13]. Moderate-intensity exercise was performed in sessions of 40 min a day, three times a week, for eight weeks (from PND31 to 87), according to the following protocol [14]: 5 min warming up at a speed of 12 ± 2 m/min, 30 min at a main speed of 20 ± 2 m/min, and 5 min cooling down at a speed of 12 ± 2 m/min.…”
Section: Exercise Programmentioning
confidence: 99%
“…type of exercise, intensity, volume, and periodization) and their different effects throughout the organism still limit the exercise-induced hormesis understanding 38 . Thereby, our laboratory has investigated the benefits of exercise in tissue-dependent oxidative stress [39][40][41][42] , and recently, we demonstrated that daily moderate physical exercise applied at juvenile ages, can decrease the risk of developing CVD by improving cardiac mitochondrial function and oxidative stress resilience in male rats 43 .…”
Section: Introductionmentioning
confidence: 99%